1992
DOI: 10.1021/bp00018a008
|View full text |Cite
|
Sign up to set email alerts
|

Concentrating Cellulases from Fermented Broth Using a Temperature‐Sensitive Hydrogel

Abstract: A temperature‐sensitive poly(N‐isopropylacrylamide) hydrogel was used to concentrate cellulases from the fermentation broth of Trichoderma reesei. The steady‐state gel volume was less and the gel collapse temperature was lower in fermented broth compared to those in water. Upon a long (24 h) temperature swing for gel swelling, a gel with lower monomer and cross‐linker content showed a larger volume increase, and it took longer to reach a constant volume which was smaller than the steady‐state volume. Upon a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Thus, depending on the heat transfer characteristics of the synthelivery, 16 immobilized-enzyme reactors, [17][18][19] and separation processes. [20][21][22][23][24][25][26] For example, when a sis molds, PNIPA gels with various structures may be obtained from the same starting monomer shrunken PNIPA gel is added to a dilute protein solution, the gel swells and absorbs water and solution. 31 Furthermore, the presence of impurities in NIPA monomer purchased from the supother small molecules; while macromolecules, such as proteins, are not absorbed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, depending on the heat transfer characteristics of the synthelivery, 16 immobilized-enzyme reactors, [17][18][19] and separation processes. [20][21][22][23][24][25][26] For example, when a sis molds, PNIPA gels with various structures may be obtained from the same starting monomer shrunken PNIPA gel is added to a dilute protein solution, the gel swells and absorbs water and solution. 31 Furthermore, the presence of impurities in NIPA monomer purchased from the supother small molecules; while macromolecules, such as proteins, are not absorbed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hydrogel ultrafiltration process did not appear useful for concentrating cellu!ase enzymes because separation efficiency was only 30 -40% (Park and Orozco-Avila, 1992). This study showed that enzyme separation efficiency could be increased to 84% if the gel was allowed to swell at a lower temperature of 20"C or below.…”
Section: Introductionmentioning
confidence: 88%
“…solutions [4][5][6][7][8][9][10] . Concentrating such solutions is important due to the wide variety of biological and synthetic materials existing or produced as very dilute solutions.…”
Section: (D) Backgroundmentioning
confidence: 99%
“…PNIPA hydrogels are probably the most widely studied of this class of material and have previously been used for concentrating dilute aqueous solutions of soluble macromolecules 5,8,11) . However, the concentrating capacity is limited due to the low swellability of the network.…”
Section: (D) Backgroundmentioning
confidence: 99%